2014
DOI: 10.1590/0104-1169.3451.2486
|View full text |Cite
|
Sign up to set email alerts
|

Nasal septum injury in preterm infants using nasal prongs

Abstract: OBJECTIVE: to assess the incidence and risk factors associated with nasal septum injury in premature infants using reused and new nasal prongs. METHOD: the study was a cohort from an open therapeutic intervention. The sample included 70 infants with a gestational age inferior to 37 weeks, who used nasal prongs and were hospitalized at the neonatal service of a hospital in Recife-PE, in the Northeast of Brazil. The data were collected in patient files through the assessment of the application of the device and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 16 publications
4
40
0
3
Order By: Relevance
“…However, binasal prongs are associated with complications such as increased resistance to gas flow, peri‐nasal leak, and nasal trauma . Observational studies have reported nasal injury in 62.9‐68.1% of preterm infants on non‐invasive ventilation with nasal prongs . The high incidence of nasal injuries associated with nasal prongs have led to the emergence of newer generation anatomically shaped nasal masks, designed using 3D facial scanning.…”
Section: Introductionmentioning
confidence: 99%
“…However, binasal prongs are associated with complications such as increased resistance to gas flow, peri‐nasal leak, and nasal trauma . Observational studies have reported nasal injury in 62.9‐68.1% of preterm infants on non‐invasive ventilation with nasal prongs . The high incidence of nasal injuries associated with nasal prongs have led to the emergence of newer generation anatomically shaped nasal masks, designed using 3D facial scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluated the incidence of lesions, specifically of the nasal septum in preterm infants caused by the use of nasal prongs. The study identified a large number of newborns developed lesions and the with a significance for the length of device usage time (Bonfim, Vasconcelos, Sousa, Silva, & Leal, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mantener un cuidado especial sobre la posición del recién nacido evita el uso de accesorios para la oxigenación. Con el solo cambio de posición y rotando la cabeza de manera alterna, se mantiene permeable la vía aérea y disminuye la severidad de las lesiones del tabique nasal [1,29].…”
Section: Discussionunclassified
“…Se evidencia que existe menor riesgo de desplazamiento de prongs con el uso de placas de hidrocoloide, el gel silicón [9,20,29], así como el protector cutáneo, a n de evitar la fricción directa de las prongs con la columela y el tabique. De esta manera, es visible el cuidado individual del neonato y cómo es un arte conjugar la ciencia con el sentido cotidiano del profesional de enfermería en benecio del confort del neonato [19,24,28].…”
Section: Discussionunclassified
See 1 more Smart Citation